PERHITUNGAN AKTUARIA MANFAAT PENSIUN-NORMAL SUKU BUNGA VASICEK MENGGUNAKAN METODE ENTRY AGE NORMAL - YUDA, WIMAS ASTARI; WIDANA, I NYOMAN; SUMARJAYA, I WAYAN (E-Jurnal Matematika; Vol 7 No 2 (2018)DO - 10.24843/MTK.2018.v07.i02.p195, 2018)
Vasicek is one of the stochastic interest rate models that can figure out  fluctuating interest rate movements. This study aims to determine the actuarial calculation of normal contributions and actuarial liability with Vasicek interest rates using entry age normal (EAN) method. Based on the calculation of normal contribution and actuarial liability with Vasicek interest rate using this  method for normal retirement age of 56 years obtained a smaller value than using constant interest rate.